2016
DOI: 10.15517/rbt.v64i1.18237
|View full text |Cite
|
Sign up to set email alerts
|

Abundancia relativa de la zorra gris Urocyon cinereoargenteus (Carnívora: Canidae) en la zona centro de Veracruz, México

Abstract: Relative abundance of the gray fox Urocyon cinereoargenteus (Carnívora: Canidae) in Veracruz central area, Mexico. The gray fox, Urocyon cinereoargenteus, is a medium-size canid widely distributed in México. Most studies on this species focus on habitat use, home range, diet, intraguild competence, and lanscape distribution between urban and rural sites. In central Veracruz, gray foxes are present in fragments of cloud forest and in shaded coffee plantations; nevertheless, its abundance has not yet been compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
9
0
4
Order By: Relevance
“…Our study demonstrates that tropical gray foxes are as flexible in their exploitation of human-influenced landscapes and resources as those inhabiting the temperate zone. However, our camera-trap data suggest that they are not habitat generalists in this region of the tropics, avoiding the interior of the dominant habitat, tropical moist broadleaf forest, sticking to the forest edge, and preferring the mosaic landscape of well-vegetated savannah, pine forest (Davis et al 2010), and agricultural lands (Gallina et al 2016). Potentially, they readily colonize new areas if suitably transformed by human activity, exploiting rodents and food waste associated with human presence, as exemplified by the presence of foxes at the Visitors' Center within the tropical broadleaf forest of a large protected area where they were absent from the interior.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our study demonstrates that tropical gray foxes are as flexible in their exploitation of human-influenced landscapes and resources as those inhabiting the temperate zone. However, our camera-trap data suggest that they are not habitat generalists in this region of the tropics, avoiding the interior of the dominant habitat, tropical moist broadleaf forest, sticking to the forest edge, and preferring the mosaic landscape of well-vegetated savannah, pine forest (Davis et al 2010), and agricultural lands (Gallina et al 2016). Potentially, they readily colonize new areas if suitably transformed by human activity, exploiting rodents and food waste associated with human presence, as exemplified by the presence of foxes at the Visitors' Center within the tropical broadleaf forest of a large protected area where they were absent from the interior.…”
Section: Discussionmentioning
confidence: 73%
“…Gray foxes thrive in both the natural as well as the humandominated landscapes of North America (Harrison 1997;Rountree 2004;Kapfer and Kirk 2012;Nogeire et al 2013;Deuel et al 2017a;Lombardi et al 2017), making them a versatile and adaptable species. Further south, they have been detected in sugarcane and coffee plantations in Mexico and upland pine forest in Belize, but generally little is known about their ecology in broadleaf forest or their adaptability to human activities in the tropics (Davis et al 2010;Gallina et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A 15year study in Mississippi using trapper harvest records reported stable trends (Lovell et al 1998). Other studies evaluating temporal variation in RAB or occupancy of this species were conducted over relatively short (<3 year) periods (Chamberlain et al 1999;Cunningham et al 2006;Gallina et al 2016). In contrast, Bauder et al (2020) found evidence of declines in Grey Foxes in Illinois over 43 years and two studies in the midwestern USA found that they were the least prevalent species in the native carnivore community (Lesmeister et al 2015;Rich et al 2018).…”
Section: J Ttmentioning
confidence: 99%
“…Distributions of RAB estimates from camera trap and transect studies were generally similar across ecoregions (Figure 3). Studies with relatively high RAB occurred in multiple ecoregions including the Temperate Sierras (Cunningham et al 2006;Gallina et al 2016) Temperate Forests (Chamberlain et al 1999), Tropical Wet Forests (Davis et al 2011), Mediterranean California (Allen et al 2017, Great Plains (Karlin & De La Paz 2015), and Marine West Coast Forests (Eriksson et al 2019). To further explore geographic variation in abundance of Grey Foxes, we calculated the rank-order of RAB or occupancy across all mammalian carnivores detected in the study, including grey fox.…”
Section: Abundancementioning
confidence: 99%
“…There were a small number of TMF articles that have investigated how populations respond to habitat degradation. From these studies, habitat fragmentation was shown to reduce the population size of birds and foxes (Husemann et al, 2015;Gallina et al, 2016). For example, the effective of population sizes of the mountain white-eye (Zosterops poliogaster) in East Africa were higher in larger and interconnected forest patches (Husemann et al, 2015).…”
Section: Effects Of Habitat Degradation On Tmf Biodiversitymentioning
confidence: 99%